2022
DOI: 10.3389/fendo.2022.951552
|View full text |Cite
|
Sign up to set email alerts
|

Integrated analysis of proteomics and metabolomics in girls with central precocious puberty

Abstract: BackgroundCentral precocious puberty (CPP) is a multifactorial and complex condition. Traditional studies focusing on a single indicator cannot always elucidate this panoramic condition but these may be revealed by using omics techniques.ObjectiveProteomics and metabolomics analysis of girls with CPP were compared to normal controls and the potential biomarkers and pathways involved were explored.MethodsSerum proteins and metabolites from normal girls and those with CPP were compared by LC-MS/MS. Multivariate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…These metabolites may participate in the formation of CPP by being involved in the regulation of lipid metabolism, suggesting that the CPP required additional energy for enhanced energy metabolism. 45 In addition, prostaglandin E2 (PGE2) together with glutathione, arachidonic acid, and 15-hydroperoxy-(5 Z ,8 Z ,11 Z ,13 E )-eicosatetraenoic acid (15-HPETE) is involved in arachidonic metabolism, as shown by metabolic pathway enrichment analysis in Fig. S19, † which can in turn promote the production of prostaglandins.…”
Section: Resultsmentioning
confidence: 99%
“…These metabolites may participate in the formation of CPP by being involved in the regulation of lipid metabolism, suggesting that the CPP required additional energy for enhanced energy metabolism. 45 In addition, prostaglandin E2 (PGE2) together with glutathione, arachidonic acid, and 15-hydroperoxy-(5 Z ,8 Z ,11 Z ,13 E )-eicosatetraenoic acid (15-HPETE) is involved in arachidonic metabolism, as shown by metabolic pathway enrichment analysis in Fig. S19, † which can in turn promote the production of prostaglandins.…”
Section: Resultsmentioning
confidence: 99%
“…Li et al. also reported that their identified DEMs in the sera of CPP girls were mainly involved in lipid and glycerophospholipid metabolism ( 18 ). More importantly, endocrine disruptors were reported to disrupt puberty, hormone sensitivity, and metabolism of glucose, fatty acids, and triglycerides in neonatal mice ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Li et al. performed analysis of proteomics and metabolomics in girls with CPP and found some key differential proteins and metabolites, including MMP9, SPP1, CDC42, POSTN, COL1A1, BMP1, and phosphocholine (16:1(9Z)/16:1(9Z)) ( 18 ). Huang et al.…”
Section: Discussionmentioning
confidence: 99%
“…These findings emphasized the potential influence of amino acid and nucleic acid metabolism on the process of precocious puberty, consistent with previous studies. 40 , 41 …”
Section: Discussionmentioning
confidence: 99%